Exploring risk factors for suicidal ideation in a population‐based sample of New Zealand women who have experienced intimate partner violence. (29th October 2013) - Gulliver, Pauline; Fanslow, Janet
Abstract Objective : To explore factors associated with suicidal thoughts among women who had experienced intimate partner violence (IPV), using data from the New Zealand replication of the WHO Multi‐country Violence Against Women study. Method : Face‐to‐face interviews were conducted. A population‐based cluster sampling scheme with a fixed number of dwellings per cluster was employed. Logistic regression was conducted to identify those variables independently associated with suicidal ideation. Results : Women who had experienced IPV were more likely to report they had thought about taking their own life if they: reported that their partner's behaviour had impacted on their mental health (OR = 4.81, 95% CI 3.30–7.01); were current or former users of recreational drugs (OR=1.94, 95% CI 1.43–2.64); had experienced a stillbirth/abortion/miscarriage (OR=1.93, 95% CI 1.44–2.58); and had experienced emotional abuse in the previous 12 months (OR=1.40, 95% CI 1.00–1.96). Conclusion and Implications : This study corroborates international findings that women's experience of IPV is associated with increased risk of suicidal thoughts. While the results point to the need for all health care providers to routinely enquire about intimate partner violence among their patients, they also argue for the need for health care providers to be aware of, and equipped to respond to, the mental health needs of their clients. The results also indicate that there is a need for mental health services to assess for, and respond to intimate partner violence among women presenting with suicidal ideation.